Electrostatically gated nanofluidic membrane for ultra-low power controlled drug delivery. Issue 9 (6th April 2020) - Di Trani, Nicola; Silvestri, Antonia; Sizovs, Antons; Wang, Yu; Erm, Donald R.; Demarchi, Danilo; Liu, Xuewu; Grattoni, Alessandro
Abstract : Control of molecular diffusion through nanofluidic channels using electrostatic gating. Abstract : Patient-centered therapeutic management for chronic medical conditions is a desired but unmet need, largely attributable to the lack of adequate technologies for tailored drug administration. While triggered devices that control the delivery of therapeutics exist, they often rely on impractical continuous external activation. As such, next generation continuously tunable drug delivery systems independent of sustained external activation remain an elusive goal. Here we present the development and demonstration of a silicon carbide (SiC)-coated nanofluidic membrane that achieves reproducible and tunable control of drug release via electrostatic gating. By applying a low-intensity voltage to a buried electrode, we showed repeatable and reproducible in vitro release modulation of three model analytes. A small fluorophore (Alexa Fluor 647), a large polymer poly(sodium 4-styrenesulfonate) and a medically relevant agent (DNA), were selected as representatives of small molecule therapeutics, polymeric drug carriers, and biological therapeutics, respectively. Unlike other drug delivery systems, our technology performed consistently over numerous cycles of voltage modulation, for over 11 days. Importantly, low power consumption and minimal leakage currents were achieved during the study. Further, the SiC coating maintained integrity and chemical inertness, shielding the membrane from degradation under simulated physiological and accelerated conditions for over 4 months. Through leveraging the flexibility offered by electrostatic gating control, our technology provides a valuable strategy for tunable delivery, setting the foundation for the next generation of drug delivery systems.